2012
DOI: 10.1100/2012/820846
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Recovery: Evaluation of a Recovery-Oriented Training Program

Abstract: Aim. This study investigates the effectiveness of a recovery-oriented training program on knowledge and attitudes of mental health care professionals towards recovery of people with serious mental illness. Methods. Using data from a longitudinal study of recovery, changes in knowledge and attitudes of 210 mental health care professionals towards recovery were explored using the Recovery Attitude Questionnaire and the Recovery Knowledge Inventory. The study uses a two-group multiple intervention interrupted tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…RKI has revealed some factors associated with recovery orientation in cross-sectional studies [ 18 20 ], as well as in longitudinal studies [ 21 ]. Appreciably, in recent years, RKI has been notably used in several interventional studies in Australia [ 22 25 ], USA [ 26 ], Canada [ 27 , 28 ], UK [ 29 ], and Netherlands [ 30 ], as various educational programs have been developed for service providers to enhance recovery orientation.…”
Section: Introductionmentioning
confidence: 99%
“…RKI has revealed some factors associated with recovery orientation in cross-sectional studies [ 18 20 ], as well as in longitudinal studies [ 21 ]. Appreciably, in recent years, RKI has been notably used in several interventional studies in Australia [ 22 25 ], USA [ 26 ], Canada [ 27 , 28 ], UK [ 29 ], and Netherlands [ 30 ], as various educational programs have been developed for service providers to enhance recovery orientation.…”
Section: Introductionmentioning
confidence: 99%
“…, Wilrycx et al . ). Further research is recommended on evaluating skills development, transfer and mastery of skills and translation of skills to practice following training (Peebles et al .…”
Section: Discussionmentioning
confidence: 97%
“…For example, Wilrycx et al . () tested the psychometric properties of the RKI and found that it was unsuitable for use in Holland (mainly due to subtleties of meaning lost in translation). An Australian study (Hungerford et al .…”
Section: Discussionmentioning
confidence: 99%
“…Personal recovery implies a client-oriented definition of recovery in which the emphasis lies more on personal development and growth than on symptom reduction. Important aspects of recovery are: hope, empowerment and the feeling of living a satisfying life despite symptoms of illness [ 8 16 ]. While recovery is an individual and subjective process, mental health care organizations can be recovery-oriented.…”
Section: Introductionmentioning
confidence: 99%